2018
DOI: 10.1097/jcn.0000000000000482
|View full text |Cite
|
Sign up to set email alerts
|

Participants’ Experiences of a Sexual Counseling Intervention During Cardiac Rehabilitation

Abstract: Background:International guidelines recommend sexual assessment and counseling be offered to all patients with cardiovascular disease during cardiac rehabilitation. However, sexual problems are infrequently addressed. The Cardiac Health and Relationship Management and Sexuality (CHARMS) intervention is a complex, multilevel intervention designed to increase the provision of sexual counseling in cardiac rehabilitation. It was piloted in 2 cardiac rehabilitation centers to assess the acceptability and feasibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(42 reference statements)
0
3
0
2
Order By: Relevance
“…Knowing the importance of the human sexual dimension and its impacts on quality of life, it is important that professionals are properly qualified to provide the necessary guidance for each patient’s query. It is possible to identify studies that demonstrated that professionals are not in the habit of discussing sexuality with patients, either because they do not feel comfortable and do not consider sexuality as a priority in care or because they have not actually undergone training to address this issue ( 32 - 33 ) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Knowing the importance of the human sexual dimension and its impacts on quality of life, it is important that professionals are properly qualified to provide the necessary guidance for each patient’s query. It is possible to identify studies that demonstrated that professionals are not in the habit of discussing sexuality with patients, either because they do not feel comfortable and do not consider sexuality as a priority in care or because they have not actually undergone training to address this issue ( 32 - 33 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The third topic addressed and which is supported by national and international guidelines is the time for resuming sexual activity, with the following recommendations: gradual resumption after seven days of hospital discharge in patients without clinical signs of ventricular dysfunction; the importance of maintaining a calm environment and being rested for sexual activity; and initially opt for positions that require less energy expenditure and facilitate breathing as well as guidance regarding the clinical signs that should be noticed by patients during and after sexual activity ( 33 , 37 , 39 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the Cardiac Health and Relationship Management and Sexuality (CHARMS) intervention study described a sexual education and support intervention for cardiac patients designed using the Behaviour Change Wheel [75]. This intervention was found to be feasible in practice [76] and acceptable to recipients [77]. There is also evidence that the Behaviour Change Wheel and related theories can be employed to create effective behaviour change interventions.…”
Section: Application Of Behavioural Science Theory In Animal Welfamentioning
confidence: 99%